The Use of Artificial Intelligence as the Potential Supporting Learning Tools for Doing Learning Projects - Iftanti, Erna; Awalin, Arpinda Syifa’a; Izza, Fatma Nuril (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Artificial Intelligence (AI) is at present getting popularly used as the supporting tools of learning. The EFL students use various types of application to support their learning and doing the school assignment and projects. This study is thus aimed at portraying how AI is used as their supporting learning tools. This narrative inquiry is carried out by asking five selected students of English Department of a state university in Tulungagung who used AI to help them completing their final project of writing thesis proposal. The data were collected through interviewing them and reading their notes in July 2023. They were then qualitatively analysed. The results of this study revealed two main points. They do not only use Chat GPT as the most popular AI application, but there are also some other AI applications like Bing Chat, and Grammarly which are used to support their learning projects like writing research proposal. Those application are used for various reasons and usage like using Chat GPT to find framework of research topic, to develop and brainstorm ideas; employing Bing Chat to find review literature; and Grammarly is used to check the grammar error in their research proposal. Surprisingly, they can learn in a joyful learning atmosphere as well because they can play games while learning English vocabulary and other topics. Finally, these research results can be pedagogically implemented in the recent English Language Teaching which integrates technology for their teaching and learning process.